Lyme borreliosis: biology, epidemiology and control - Gray, J.; Gray, J.; Kahl, O.; Kahl, O.; Lane, R. S.; Lane, R. S.; Stanek, G.; Stanek, G. (Wallingford :CABI Publishing, 2002)
This book contains 12 chapters. The first chapter outlines the historical and clinical aspects of Lyme borreliosis including descriptions of the disease in humans and domestic animals, and of diagnosis and treatment. The second chapter deals with ecological methods and terminology and chapters 3-5 describe the biology of the spirochaetes and their behaviour in vectors and vertebrates. The next 4 chapters (6-9) concern the ecology of Borrelia burgdorferi in Europe, Russia, South East Asia and North America, and the last 3 chapters (10-12) deal with the application of the biological and ecological attributes of the pathogens to disease epidemiology, vaccine development and ecological management of Lyme borreliosis.
Keywords: HH200 - Environmental Pest Management; HH600 - Host Resistance and Immunity; LL821 - Prion, Viral, Bacterial and Fungal Pathogens of Animals, (New March 2000); LL823 - Veterinary Pests, Vectors and Intermediate Hosts, (New March 2000); LL886 - Diagnosis of Animal Diseases, (New March 2000); VV210 - Prion, Viral, Bacterial and Fungal Pathogens of Humans, (New March 2000); VV230 - Public Health Pests, Vectors and Intermediate Hosts, (New March 2000); VV720 - Diagnosis of Human Disease, (New March 2000); YY700 - Pathogens, Parasites and Infectious Diseases (Wild Animals), (New March 2000); ZZ333 - Microbial Ecology, (New March 2000); ZZ390 - Microbiology (General); Europe; North America; Russia; South East Asia